(untitled) (KYAMC Journal, 2021)
Background: Third molar is the most commonly impacted tooth in the oral cavity and accounts for large of all impactions. The most common complication in the extraction of the third mandibular molars is nerve and vessels damage. Therefore, thorough radiographic assessment is a necessary to avoid these surgical complications. Objective: The purpose of this study was to evaluate the frequency, angulation, depth of the impacted mandibular third molars and its relationship with ramus on radiographs. Materials and Methods: This study comprised 800 orthopantomograms (OPGs) of patients attending different dental clinics and hospitals in Rangpur region, Bangladesh between June 2014 to May 2015. Panoromic Radiographic assessment was carried out to evaluate the pattern of third molar impaction in terms of age, gender, angulation of impaction, level of eruption and available retromolar space using panoramic radiographs and Pell & Gregory classification. Results: A total of 314 radiographic third molar areas were found in this study, out of them 137 belong to male patients and 177 belong to the female patients. The mesio angular types of angulation was most prevalent (46%) whereas distoangular was rare (5%) in our study. In relation to anterior border of the ramus of mandible Level B 52% and Class II 59% were the most common pattern of impaction. The female tends to be dominant as compared to male & the maximum number (35%) of impacted third molars are found in an age group of 38 years and above. Conclusion: Panoramic radiographs can be used as reliable investigation for evaluation of impacted mandibular third molar. KYAMC Journal.2021;12(01): 08-13